2016
DOI: 10.1177/1099636215603692
|View full text |Cite
|
Sign up to set email alerts
|

Single- and double-layer aluminum corrugated core sandwiches under quasi-static and dynamic loadings

Abstract: The crushing of single-and double-layer zig-zag trapezoidal corrugated core sandwiches was investigated experimentally and numerically at quasi-static and dynamic rates. The buckling stress of sandwiches increased when the rate increased from quasi-static to dynamic. The increased buckling stresses were ascribed to the micro-inertial effects, which altered the buckling mode of the core from three plastic hinges to higher number of plastic hinge formations. The initial buckling stress was numerically shown to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Several innovative designs of corrugated structures have been proposed in the past few years expanding their range of potential applications. Examples of novel core designs are integrated woven corrugated cores, hierarchical corrugated cores, zig‐zag trapezoidal corrugated core, two way corrugated cores, bi‐corrugated plate cores, and bi‐directional corrugated‐strip‐cores . The categorization of corrugated structures is summarized in Figure , and is discussed in detail in the following sections.…”
Section: Corrugated Coresmentioning
confidence: 99%
“…Several innovative designs of corrugated structures have been proposed in the past few years expanding their range of potential applications. Examples of novel core designs are integrated woven corrugated cores, hierarchical corrugated cores, zig‐zag trapezoidal corrugated core, two way corrugated cores, bi‐corrugated plate cores, and bi‐directional corrugated‐strip‐cores . The categorization of corrugated structures is summarized in Figure , and is discussed in detail in the following sections.…”
Section: Corrugated Coresmentioning
confidence: 99%
“…It was shown that foam filling affected the buckling mode of core. Few studies on the modelling static and dynamic deformation of corrugated sandwiches with single and double‐layer have also been published, such as refs . Nevertheless, the effect of imperfections particularly on the shock mode of deformation multilayer corrugated structures at increasing impact velocities has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…A corrugated core offers a variety of benefits, including ease of manufacturing, heat dissipation, high structural performance, and the capability of resistance to bending and twisting, in addition to vertical shear. In this regard, in order to characterize different features of structural performance of this type of sandwich structures, a considerable number of studies have been carried out, including bending behavior [1823], out-of-plane compression [2427], and impact response [2831]. Due to the mechanical performance superiority of filled corrugated core sandwiches over the traditional sandwich structures with empty corrugated core, several relevant investigations have been conducted recently.…”
Section: Introductionmentioning
confidence: 99%